Bis(imino)carbazolate: A Master Key for Barium Chemistry. (24th March 2020) - Chapple, Peter M.; Kahlal, Samia; Cartron, Julien; Roisnel, Thierry; Dorcet, Vincent; Cordier, Marie; Saillard, Jean‐Yves; Carpentier, Jean‐François; Sarazin, Yann
Abstract: Reported here is a readily available bis(imino)carbazole‐based proligand that constitutes a convenient entry point into the challenging synthetic molecular chemistry of barium. It enables the preparation of rare or even, up to now, unknown, solution‐stable heteroleptic barium complexes. The syntheses and structural features for the first molecular barium fluoride and the first barium stannylide, with an unsupported Ba−Sn bond, are described, along with other carbazolate barium species: an amide (both a remarkably stable starting material and an excellent hydrophosphination precatalyst), iodide, and silanylide. DFT analysis of bonding patterns in the barium stannylide and barium silanylide highlights a prevailingly ionic barium–tetrelide bond with a small covalent contribution. Abstract : Barium rockt ! Eine neuer Carbazol‐basierter Ligand, der leicht in großen Mengen erhalten werden kann, ermöglicht die Synthese von bislang unbekannten lösungsstabilen Bariumkomplexen. Beispiele sind Bariumfluorid‐ und Bariumstannylid‐Spezies, die ungewöhnliche Bindungsmuster aufweisen.